Energy Price Uncertainty and Investment: Firm Level Evidence from Indian Manufacturing Sector - Acharya, Rajesh H.; Sadath, Anver C. (International Journal of Energy Economics and Policy, 2016)
Uncertainty whatsoever has undoubtedly been deemed to be malevolent to the interests of investors. Theories of partial irreversibility of investment argue that uncertainty at the micro level negatively impacts the firm’s investment and thereby, at least, slow the process of capital accumulation. Therefore, the present study, empirically analyzes how energy price uncertainty affects investment decisions of manufacturing firms in India. A variety of panel data models are estimated using Generalized Method of Moments (GMM) with data pertaining to Indian manufacturing firms over the period 1992- 93 to 2013- 14. Results are consistent with irreversible investment literature on the supply side of production, which shows that energy uncertainty has a negative effect on the capital accumulation in the manufacturing sector and this effect transpires in the form of firm’s inability to adjust its actual capital stock to match up to its potential desired capital stock as proposed by the investment theories. Keywords: Energy Price Uncertainty, Irreversible Investment, Energy Intensity JEL Classifications: C23, D80, E20, Q41.